Determinant Factors Of Early Marriage On Adolescent Reproductive Health In Madura Island - Permatasari, Dian; Suprayitno, Emdat; Yasin, Zakiyah (Poltekkes Kemenkes Surakarta, 2023)
Background: Early marriage is a problem at the national level in Indonesia. Madurese society has the second highest rate of early marriage in Madura, thus potentially causing poverty and health problems such as teenage pregnancy, labor pain, and death. This study aimed to determine the factors that influence adolescents' knowledge about early marriage. Methods: The variables in this study are gender, education, and place of residence. The analysis in this study is to predict the outcome of the dependent variable, which is categorically based on one or more independent variables. The respondents to this study were teenagers aged 15–19. The number of respondents in this study was 100 respondents with random sampling. The instrument used is a questionnaire about early marriage. With significance criteria in the range r = 0.2000.543, table r = 0.362, and a confidence value of Cronbach's alpha = 0.823. The data were analyzed with the Chi-Square test. Results: The results of the Chi-Square analysis obtained a p-value of 0.000 <0.05, which means that there is a significant relationship between education and knowledge about early marriage. Analysis of the relationship between the two variables shows an OR value of 0.09, meaning that adolescents with higher education have 0.09 times less knowledge of early marriage than adolescents with low education. Conclusion: Access to information is a problem that affects the knowledge of adolescents about the risks of early marriage, so adolescents with low education have less knowledge about the risks of early marriage.